If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11 + -8r = 7(r + 1) Reorder the terms: -11 + -8r = 7(1 + r) -11 + -8r = (1 * 7 + r * 7) -11 + -8r = (7 + 7r) Solving -11 + -8r = 7 + 7r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-7r' to each side of the equation. -11 + -8r + -7r = 7 + 7r + -7r Combine like terms: -8r + -7r = -15r -11 + -15r = 7 + 7r + -7r Combine like terms: 7r + -7r = 0 -11 + -15r = 7 + 0 -11 + -15r = 7 Add '11' to each side of the equation. -11 + 11 + -15r = 7 + 11 Combine like terms: -11 + 11 = 0 0 + -15r = 7 + 11 -15r = 7 + 11 Combine like terms: 7 + 11 = 18 -15r = 18 Divide each side by '-15'. r = -1.2 Simplifying r = -1.2
| -11-8r=7r+7 | | .4y=16 | | 0.4(6x+12)=1.4-(x+2) | | 99-(6x+16)=6(x+3)+x | | 5(6z-1)-3(z+3)=17(z+1) | | -3v-(3v-5)=-3v-1 | | -1+b=3(2b-3) | | 4(-6k+2)=4(-10+5k)-3k | | 4(5a+2)=-10a+4 | | -2=-2b-(-6b+3) | | 3=-4(1-5a)-10a | | -9=-7a-(8a+3) | | 2x-y=7 | | -5p-5(-3+3p)=-8 | | 3(-5x+3)+5=6+x | | .75(8z-12)=.833333333(12z-18) | | -4(-10m+3)=-(-7-8m) | | 41-(2x+4)=2(x+6)+x | | 8(7)=x | | -m-(3m+1)=2m+9 | | -7+3v=4(3v+3) | | 4(k+2)=2(-3+9k)+2k | | -(-8n+1)=-5n-1 | | 8x-2=6x+8x+4 | | -6=3m+3(3m+3) | | 19x+3=15x+24x+5 | | 3h+2j-c(3h-8j+7k)= | | 3(x+21)=-4(x-14) | | -6=3(2+6m)+m | | 10x+4=11x-7 | | 9=-6p-6(p+3) | | 9x+1=6x-7x+4 |